Knowledge, Attitudes, and Practices Toward Coronavirus and Associated Anxiety Symptoms Among University Students: A Cross-Sectional Study During the Early Stages of the COVID-19 Pandemic in Bangladesh - Patwary, Muhammad Mainuddin; Disha, Asma Safia; Bardhan, Mondira; Haque, Md. Zahidul; Kabir, Md. Pervez; Billah, Sharif Mutasim; Hossain, Md. Riad; Alam, Md. Ashraful; Browning, Matthew H. E. M.; Shuvo, Faysal Kabir; Piracha, Awais; Zhao, Bo; et al. (Frontiers in Psychiatry, 2022)
Background University students’ knowledge, attitude, and practice (KAP) toward COVID-19 are vital to prevent the spread of the virus, especially in the context of developing countries. Consequently, the present study aimed to determine the KAP levels of university students and associated anxiety during the earlier stage of the pandemic in Bangladesh. Methods A cross-sectional, online study with 544 university students was conducted during April 17–May 1, 2020. The questionnaire incorporated several KAP-related test items aligned with the World Health Organization (WHO) guidelines. Anxiety was measured with the 2-item Generalized Anxiety Disorder scale (GAD-2). Multivariable logistic regression analysis was performed to determine the association between KAP levels and anxiety adjusting for sociodemographic variables. Subgroup analyses included rerunning models stratified by gender and quarantine status. Results Approximately 50% of students showed high levels of knowledge about COVID-19 guidelines, 59% reported behavioral practices that aligned with COVID-19 guidelines, and 39% had negative attitudes toward COVID-19 guidelines. Attitudes differed by anxiety (χ2 = 23.55, p < 0.001); specifically, negative attitudes were associated with higher anxiety (OR: 2.40, 95% CI = 1.66–3.46, p < 0.001). Associations were significant for male (OR = 2.36; 95% CI = 1.45–3.84, p < 0.001) and female (OR = 2.45; 95% CI = 1.3–4.34; p < 0.001) students. Stratified analyses found non-quarantined students with negative attitudes had three times the chance of experiencing anxiety (OR = 3.14, 95% CI: 1.98–4.98, p < 0.001). Non-quarantined students with low levels of knowledge had half the chance of developing anxiety (OR = 0.49, 95% CI: 0.31–0.78, p < 0.01). Conclusion Based on these findings, it is recommended that university authorities continue to prioritize proactive and effective measures to develop higher levels of knowledge, more positive attitudes and better behavioral practices regarding COVID-19 for the mental health of their students.